2003
DOI: 10.1021/la026755w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Interior of Aqueous Reverse Micelles:  A Comparison between Sodium and Potassium Counterions

Abstract: We present the results of a molecular dynamics simulation study of the effects of counterion type on the properties of the interior region of aqueous reverse micelles. The model systems, which treat only the interior region at the atomistic level, are designed to represent water-in-oil microemulsions formed by the aerosol-OT surfactant, either with its usual counterion, Na + , or with the K + counterion. Our study covers the water content, w0 ) [H2O]/[surfactant], range of 1-7.5, where the reverse micelles are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 39 publications
8
123
0
Order By: Relevance
“…[13-16, 31, 37-40, 58] In the present RMs, the Na + counterion can accommodate six coordinating water molecules in its solvation shell. [15,38,39,59] Therefore, the number of water molecules required to fully solvate an AOT head group and its counterion in RMs is certainly much more than three. [26,28,40,42,60] FTIR studies by Jain et al [42] indicated that the AOT molecule can be hydrated by a maximum of 12 water molecules.…”
Section: Ftir Spectroscopic Studiesmentioning
confidence: 99%
“…[13-16, 31, 37-40, 58] In the present RMs, the Na + counterion can accommodate six coordinating water molecules in its solvation shell. [15,38,39,59] Therefore, the number of water molecules required to fully solvate an AOT head group and its counterion in RMs is certainly much more than three. [26,28,40,42,60] FTIR studies by Jain et al [42] indicated that the AOT molecule can be hydrated by a maximum of 12 water molecules.…”
Section: Ftir Spectroscopic Studiesmentioning
confidence: 99%
“…Experimental and modeling studies 22,34,[36][37][38][39] suggest that there is a layered water pool structure where some water molecules are associated with surfactant head groups, some form an intermediate layer consisting of the next few nearest neighbors and, in the case of large reverse micelles, an interior region containing bulk water. From this standpoint, it is possible that, in the reverse micelles with low amounts of added water, most of the water molecules strongly associated with the AOT head groups.…”
Section: Influence Of Ferrous Sulfate and Water On Lipid Oxidationmentioning
confidence: 99%
“…Recently, molecular dynamic simulations (MD) have been successfully used to gather additional information about AOT RM structure and dynamics at the atomic level [9][10][11][12][13][14][15][16] . These studies have underlined the effect of the charged, restricted microenvironment on the confined water structural 13,14,16 and dynamical properties 13,14,17 existing in RM.…”
Section: Introductionmentioning
confidence: 99%